Measuring the inclination and mass-to-light ratio of axisymmetric galaxies via anisotropic Jeans models of stellar kinematics - Cappellari, M (2008)
We present a simple and efficient anisotropic generalization of the semi-isotropic (two-integral) axisymmetric Jeans formalism, which is used to model the stellar kinematics of galaxies. The following is assumed: (i) a constant mass-to-light ratio (M/L) and (ii) a velocity ellipsoid that is aligned with cylindrical coordinates (R, z) and characterized by the classic anisotropy parameter. Our simple models are fit to SAURON integral-field observations of the stellar kinematics for a set of fast-rotator early-type galaxies. With only two free parameters (βz and the inclination), the models generally provide remarkably good descriptions of the shape of the first (V) and second () velocity moments, once a detailed description of the surface brightness is given. This is consistent with previous findings on the dynamical structure of these objects. With the observationally motivated assumption that βz ≳ 0, the method is able to recover the inclination. The technique can be used to determine the dynamical M/L and angular momenta of early-type fast-rotators and spiral galaxies, especially when the quality of the data does not justify more sophisticated modelling approaches. This formalism allows for the inclusion of dark matter, supermassive black holes, spatially varying anisotropy and multiple kinematic components. © 2008 RAS.